Development and validation of patient satisfaction instrument - Abd. Manaf, Noor Hazilah; Mohd, Dinon; Abdullah, Kalthom (Emerald, 2012)
Purpose: Patient satisfaction of healthcare organisation is often used as a measure of organisational efficiency. However, there is a need for valid and reliable instruments to be used in order to ensure that the findings are accurate. This paper explores the development and validation of an outpatient satisfaction instrument, with emphasis on the service of the attending physician. Design/methodology/approach: Twenty-six items on service of the attending physician and registration service were developed for the instrument based on earlier published research. The instrument was applied to a cross-sectional study and data collected was factor analysed to ascertain construct validity, while reliability was established by assessing the internal consistency. Findings: The instrument was found to establish excellent reliability with Cronbach’s alpha 0.975, and two factors ‘service of doctors’ and ‘registration service’ were extracted from the factor analysis. Research limitations/implications: A valid and reliable instrument on the service of the attending physician and the registration encounter prior to consultation was established. The instrument does not measure other outpatient services such as laboratory service which could be considered for future research. Practical implications: The patient satisfaction instrument can be used by healthcare organisations in other settings due to its strong psychometric properties.